2011
DOI: 10.9734/ajea/2011/339
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Effects of Planting Dates on Growth and Yield of 18 Corn Hybrids (Zea mays L.)

Abstract: In this study 18 new corn varieties consist of 15 foreign early and mid-mature single cross hybrids and 3 Iranian commercial hybrids (KSC704, KSC647and DC370) were evaluated at two sowing date (5 and 20 June) based on RCBD with 3 replications at Khorasan Razavi Agricultural Research Centre, Mashhad, Iran on 2009. This study showed that among all hybrids, EXP1 (16.03 ton/ha) and OSSK617 (15.51 ton/ha) had the highest yields in early planting (5 June) and EXP1 (16.52 ton/ha) and KDC370 (16.22 ton/ha) produced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
2
7
1
Order By: Relevance
“…This can be attributed to the fact that delayed sowing results in the reduction of photoperiod which ultimately results in the decrease in the number of leaves. The results are confirmed by Beiragi et al, (2011) who reported that the total number of leaves decreased with delayed sowing. Number of functional leaves plant -1 was higher with wider spacing compared to narrow spacing (Table 4).…”
Section: Resultssupporting
confidence: 77%
“…This can be attributed to the fact that delayed sowing results in the reduction of photoperiod which ultimately results in the decrease in the number of leaves. The results are confirmed by Beiragi et al, (2011) who reported that the total number of leaves decreased with delayed sowing. Number of functional leaves plant -1 was higher with wider spacing compared to narrow spacing (Table 4).…”
Section: Resultssupporting
confidence: 77%
“…The findings indicate that the optimum sowing date also resulted remarkably improved cob length. This might be due to appropriate time of sowing; as according to findings of [14] delay planting reduces kernel weight, kernel number ofcob1 and cob length.…”
Section: Resultsmentioning
confidence: 99%
“…Rainfall patterns and other weather conditions associated with different planting dates have a modifying effect on length of the growing season, maize development and harvesting period (Beiragi et al, 2011). Maize yield response to planting date is very similar in different years and locations attributing yield benefits to early planting (Good et al, 2015;Nafziger, 2008).…”
Section: Introductionmentioning
confidence: 99%